Contemporary Subsidence and Ground Movement, Southwestern Ontario: Possible Bedrock Controls - Veldhuyzen, Hendrik (Géographie physique et Quaternaire, 1993)
ABSTRACT Ground movement, principally subsidence with limited strike-slip displacement, occurs discontinuously along an 8 km-long, north-south zone which is subparallel to the St. Clair River and extends from Mooretown to Corunna, Ontario. The southern-most area of subsidence lies beneath the river, 25 m from the Canadian shore. The longest continuous interval of subsidence is ^ 75 m east of the river and the northern limit is located about 250 to 300 m east of the river. Subsidence has been both abrupt and gradual, occurring overnight and over a two-year period. In the south and central areas the west side (the side closer to the river) has dropped 20 to 40 cm. However, in the north, the east side has subsided. The foundation of one home has been displaced 1 and 5 cm, in a right-lateral sense, along two discrete surfaces. The ground movements do not resemble surface slumping. Bedrock movement resulting from either dissolution of limestone or salt, displacements along Grenville basement structures, or a combination of the two may explain the phenomenon. The deformation observed, both in the production of scarps and damage to civil structures, may have neotectonic implications.